Gestão autônoma da medicação para promoção do cuidado seguro em atenção psicossocial - Pinho, Eurides Santos (2023)
INTRODUCTION: Autonomous Medication Management (GAM) enables the co-management of drug treatment by users of mental health services and influences quality and safe care. In Psychosocial Care, the prescription of psychotropic drugs is a care action that focuses on the biological, on the biochemical alterations of psychiatric illnesses without considering the biopsychosocial context of the users. The consumption of psychotropic drugs sometimes disregards the user's participation in conducting the treatment itself. There is evidence of improvements in the context of psychosocial care through investment in the co-management of drug therapy with user involvement in decision-making processes. OBJECTIVE: To analyze, from the perspective of mental health team professionals, the practices of Autonomous Medication Management to promote user involvement in safe care, in psychosocial care. METHOD: This is an intervention-research with a qualitative approach, conducted in four Psychosocial Care Centers in a municipality in the central west region of Brazil, which had the participation of 56 professionals from the teams and health. Data were collected in two stages, the first between May and June 2021 through a questionnaire and semi-structured interview, and the second in August 2022 from the offer of a training process on the autonomous management of medication associated with the perspective of promoting user involvement in safe care. The emerging data were organized using the ATLAS.ti.6.0 software and submitted to content analysis, thematic modality. RESULTS: The GAM is an educational process that encompasses users and professionals. The results of this research were summarized in three categories: Perceptions of professionals about the co-management of drug therapy; Harmless medication in the context of mental health care; Autonomous Medication Management: perspectives for safe care. It was evidenced that the professionals' perception of the demand to involve the user in the decision of drug therapy transits between views based on the hegemony of the biomedical model, which reinforces adherence to the use of psychotropic drugs, between the challenges and existing actions for user involvement and the reformist ideals based on the model of psychosocial care. As actions and challenges to promote co-management, the indiscriminate and inappropriate use of psychotropic drugs and access to information about medications were perceived as intervening in harmless medication and safe care. Autonomous Medication Management was pointed out by professionals with the potential to provide safe care, given the possibilities of carrying out psychoeducational approaches on psychotropic drugs, valuing the participation of family members/caregivers and overcoming obstacles to the involvement of users in medication co-management. FINAL CONSIDERATIONS: The GAM is based on the psychosocial care model, encourages the development of actions that promote co-management through the user's involvement in their treatment and, consequently, provides reflection on their autonomy and protagonism in the face of drug therapy to achieve safe care , in the context of psychosocial care and, more broadly, in mental health.